Targeted next generation sequencing directly from sputum for comprehensive genetic information on drug resistant Mycobacterium tuberculosis. (March 2021) - Kambli, Priti; Ajbani, Kanchan; Kazi, Mubin; Sadani, Meeta; Naik, Swapna; Shetty, Anjali; Tornheim, Jeffrey A.; Singh, Harpreet; Rodrigues, Camilla
Abstract: Background: Timely drug resistance detection is essential to global tuberculosis management. Unfortunately, rapid molecular tests assess resistance to only a few drugs, with culture required for comprehensive susceptibility test results. Methods: We evaluated targeted next generation sequencing (tNGS) for tuberculosis on 40 uncultured sputum samples. Resistance profiles from tNGS were compared with profiles from Xpert MTB/RIF, line probe assay (LPA), pyrosequencing (PSQ), and phenotypic testing. Concordance, sensitivity, specificity, and overall test agreement were compared across assays. Results: tNGS provided results for 39 of 40 samples (97.5%) with faster turnaround than phenotypic testing (median 3 vs. 21 days, p = 0.0068). Most samples were isoniazid and rifampin resistant (N = 31, 79.5%), 21 (53.8%) were fluoroquinolone resistant, and 3 (7.7%) were also resistant to Kanamycin. Half were of the Beijing lineage (N = 20, 51.3%). tNGS from uncultured sputum identified all resistance to isoniazid, rifampin, fluoroquinolones, and second-line injectable drugs that was identified by other methods. Agreement between tNGS and existing assays was excellent for isoniazid, rifampin, and SLDs, very good for levofloxacin, and good for moxifloxacin. Conclusion: tNGS can rapidly identify tuberculosis, lineage, and drug resistance with faster turnaround than phenotypic testing. tNGS is a potential alternative to phenotypic testing in high-burden settings.